Does resveratrol favor peri-implant bone repair in rats with ovariectomy-induced osteoporosis? Gene expression, counter-torque and micro-CT analysis - Rodrigo Soler ZAMAI; Monica Grazieli CORRÊA; Fernanda Vieira RIBEIRO; Fabiano Ribeiro CIRANO; Marcio Zaffalon CASATI; Michel Reis MESSORA; Suzana Peres PIMENTEL (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract This study investigated the influence of resveratrol on peri-implant repair and its effects on bone-related markers in ovariectomy-induced osteoporosis in rats. Animals were divided into: OVX+PLAC (n = 10): ovariectomized animals treated with placebo; OVX+RESV (n = 10): OVX treated with resveratrol; OVX+PLAC+ZOL (n = 10): OVX treated with PLAC and zoledronate; OVX+RESV+ZOL (n = 10): OVX treated with RESV and ZOL; and SHOVX+PLAC (n = 10): sham ovariectomy treated with PLAC. RESV and PLAC were administrated after ovariectomy and ZOL after six weeks after OVX, until the end of experiment. One implant was inserted in each tibiae of animals 18 weeks after ovariectomy. After 4 weeks, one implant was removed for counter-torque, and peri-implant tissue was collected for mRNA quantification of several osteogenic markers by PCR. The other tibia was submitted to micro-computed tomography analysis. Reduced counter-torque values, bone-implant contact (BIC) and bone volume fraction (BV/TV), and higher bone porosity (BP) were detected in OVX+PLAC group when compared to SHOVX+PLAC (p < 0.05). OVX+RESV rats presented lower BIC, BV/TV, and trabecular number (Tb.N), and augmented BP and trabecular spacing (Tb.Sp) when compared to SHOVX+PLAC (p < 0.05). Higher Tb.N and connectivity density (Conn.Dn) and reduced Tb.Sp were observed in OVX rats treated with ZOL, independently of RESV, when compared to OVX+PLAC and OVX+RESV groups (p < 0.05), whereas the combination ZOL+RESV promoted lower BP when compared to OVT+PLAC and OVX+RESV (p < 0.05). Gene expression was not influenced by RESV (p > 0.05), whereas ZOL promoted up-regulation of BMP-2 (p<0.05). RESV did not improve peri-implant bone repair in rats with ovariectomy-induced osteoporosis.